2014
DOI: 10.4161/rna.29947
|View full text |Cite
|
Sign up to set email alerts
|

A single molecule approach to mRNA transport by a class V myosin

Abstract: m RNA localization ensures correct spatial and temporal control of protein synthesis in the cell. We show that an in vitro single molecule approach, using purified recombinant full-length proteins and synthesized mRNA, provides insight into the mechanism by which localizing mRNAs are carried to their destination. A messenger ribonucleoprotein (mRNP) complex was reconstituted from a budding yeast class V myosin motor complex (Myo4p-She3p), an mRNA-binding adaptor protein (She2p), and a localizing mRNA (ASH1). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…They however, reached contradicting conclusions on the role of ASH1 mRNA itself, with one study concluding that the mRNA itself is essential for processivity under physiological conditions to stabilise the transport complex [ 45 ], whereas the other argued that the cargo mRNA is dispensable for in vitro processivity [ 44 ]. It therefore remains unclear if the RNA moiety is essential for transport in living cells [ 47 , 48 ].
Fig.
…”
Section: Motor Proteinsmentioning
confidence: 99%
“…They however, reached contradicting conclusions on the role of ASH1 mRNA itself, with one study concluding that the mRNA itself is essential for processivity under physiological conditions to stabilise the transport complex [ 45 ], whereas the other argued that the cargo mRNA is dispensable for in vitro processivity [ 44 ]. It therefore remains unclear if the RNA moiety is essential for transport in living cells [ 47 , 48 ].
Fig.
…”
Section: Motor Proteinsmentioning
confidence: 99%
“… 35 The authors suggest that particle movement in absence of RNA, as reported by Heym and colleagues, 28 must have been artificially induced by protein-protein interactions at low ionic-strength (50 mM KCl) conditions. The authors further suggest that “… a stable Myo4p-She3p-She2p complex does not form at 140 mM KCl in vitro and thus Myo4p would be non-motile in the cell without cargo.” 35 Unfortunately, no reference is given to substantiate this statement and to our knowledge no experiment has been published that directly assesses the SHE-complex assembly at different salt concentrations. The aim of this study is to test whether zip-code RNA is indeed required to assemble the Myo4p-containing transport complex at physiologic salt concentrations and temperature.…”
Section: Introductionmentioning
confidence: 90%